2013
DOI: 10.1109/ted.2013.2278201
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance and Robust SRAM Cell Based on Asymmetric Dual-$k$ Spacer FinFETs

Abstract: This paper proposes a new asymmetric underlap Fin-Field Effect Transistor (FinFET) structure using a dual-k spacer. Asymmetric dual-spacer at source shows excellent gate control over the channel due to increase in the outer fringe field at gate/source underlap. Hence, this structure exhibits a superior short-channel effect metric over the conventional/single-spacer underlap FinFET. The proposed asymmetric structure enhances static random access memories (SRAMs) performance in terms of robustness, access times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Major manufacturing companies like Intel and TSMC have adopted FinFET in their 22-nm technology node while others are expecting to use it in the near future [1,2]. This advancement in technology facilitates highly energy efficient electronics and a long battery lifetime in both low power (LP) and high performance (HP) operating regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major manufacturing companies like Intel and TSMC have adopted FinFET in their 22-nm technology node while others are expecting to use it in the near future [1,2]. This advancement in technology facilitates highly energy efficient electronics and a long battery lifetime in both low power (LP) and high performance (HP) operating regions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the underlap FinFETs have already earned very good control over SCEs [13,14]. Similarly, Pal et al [1,2] have proposed that excellent control over channel and significant improvement in I on and I off are achievable with contemplate dual-k spacers in the underlap region. This work quantitatively describes the effect of considering high-k dielectric as spacer materials in the underlap regions of a hybrid FinFET on various performance metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Only then, it was adopted as a major way forward for incorporation within IC technology (Moshgelani et al, 2012). Over the years, there were several changes that FinFET had adopted, such as structures with underlap and overlap regions as reported in various researches (Pal et al, 2013;Pal et al, 2015), and those structures with different gate materials as reported in (Hussain et al, 2010), in relation to the Fin shape and so on. Gate-all-around (GAA) FinFET is one of the most recent developments in the FinFET series having the channel surrounded from all four sides (Singh et al,Chopade & Padole 169 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial amount of research has so far been reported regarding noise margin improvement including Read/Write Noise Margins (RSNM/WSNM), Hold Static Noise margin (HSNM), data retention and yield improvement of SRAM [4][5][6], like P-P-N based 10T SRAM [7], decoupled latch [8], [9] and 5T SRAM cell [10]. Some popular methods include voltage scaling, switching activity reduction, architectural techniques, and device sizing and new device structures [11][12][13][14]. All these work analyze and quantify the impact on cell stability degradation in lifetime circuit performance.…”
Section: Introductionmentioning
confidence: 99%